Spatial Dissociation of Subretinal Drusenoid Deposits and Impaired Scotopic and Mesopic Sensitivity in AMD - Zhang, Yuhua; Sadda, SriniVas R.; Sarraf, David; Swain, Thomas A.; Clark, Mark E.; Sloan, Kenneth R.; Warriner, William E.; Owsley, Cynthia; Curcio, Christine A. (Investigative ophthalmology & visual science, 2022)
Subretinal drusenoid deposits (SDD) first appear in the rod-rich perifovea and can extend to the cone-rich fovea. To refine the spatial relationship of visual dysfunction with SDD burden, we determined the topography of mesopic and scotopic light sensitivity in participants with non-neovascular AMD with and without SDD. Thirty-three subjects were classified into three groups: normal (n = 9), AMD-Drusen (with drusen and without SDD; n = 12), and AMD-SDD (predominantly SDD; n = 12). Mesopic and scotopic microperimetry were performed using 68 targets within the Early Treatment Diabetic Retinopathy Study grid, including points at 1.7° from the foveal center (rod:cone ratio, 0.35). Age-adjusted linear regression was used to compare mesopic and scotopic light sensitivities across groups. Across the entire Early Treatment Diabetic Retinopathy Study grid and within individual subfields, the three groups differed significantly for mesopic and scotopic light sensitivities (all P < 0.05). The AMD-SDD group exhibited significantly decreased mesopic and scotopic sensitivity versus both the normal and the AMD-Drusen groups (all P < 0.05), while AMD-Drusen and normal eyes did not significantly differ (all P > 0.05). The lowest relative sensitivities were recorded for scotopic light levels, especially in the central subfield, in the AMD-SDD group. SDD-associated decrements in rod-mediated vision can be detected close to the foveola, and these deficits are proportionately worse than functional loss in the rod-rich perifovea. This finding suggests that factors other than the previously hypothesized direct cytotoxicity to photoreceptors and local transport barrier limitations may negatively impact vision. Larger prospective studies are required to confirm these observations.